Answer:
Male: Median: 64.5 and the mean is 70.6
Female: median: 83 and mean is: 79.93
Step-by-step explanation:
For median, you place all of the numbers from lowest to highest, and then find the number in the middle.
For Mean, add up all the numbers, then divide by the amount of numbers there.
For example.
30/5= 6
Answer:
please pretty please mark brainlist
Step-by-step explanation:
number of plants = 647
number of plants in 1 rows = 20
number of rows =
647 ÷ 20 = 32 and remainder = 7 =>
647 = 32 × 20 + 7 =>
647/20 =
(32 × 20 + 7) / 20 =
32 + 7/20 =
32 7/20
Answer:
a) X[bar]₁= 1839.20 cal
b) X[bar]₂= 1779.07 cal
c) S₁= 386.35 cal
Step-by-step explanation:
Hello!
You have two independent samples,
Sample 1: n₁= 15 children that did not eat fast food.
Sample 2: n₂= 15 children that ate fast food.
The study variables are:
X₁: Calorie consumption of a kid that does not eat fast food in one day.
X₂: Calorie consumprion of a kid that eats fast food in one day.
a)
The point estimate of the population mean is the sample mean
X[bar]₁= (∑X₁/n₁) = (27588/15)= 1839.20 cal
b)
X[bar]₂= (∑X₂/n₂)= (26686/15)= 1779.07 cal
c)
To calculate the sample standard deiation, you have to calculate the sample variance first:
S₁²=
[∑X₁² - (( ∑X₁)²/n₁)]=
= 149263.4571 cal²
S₁= 386.35 cal
I hope it helps!
Answer:
The three digit number = 951
Step-by-step explanation:
Let suppose the numbers are:
= abc
According to given condition:
a+ b + c = 15 -------------eq1
Also, given the difference between the first two digit = the difference between the last two digits:
==> l a-b l = l b-cl
==> (a-b) = (b-c)
==> (a+c) = 2b
Now we will substitue in eq1
==> a+ b + c = 15
==> 2b + b = 15
==> 3b = 15
Dividing both sides by 3 we get:
b =5
a + c = 2b
a+ c = 10
a = 10 -c ..........(2)
We know that"
(a-b) = (b-c)
==> a > b+c
==> a > 5 + c
==> 10 -c > 5 +c
==>5 > 2c
==> 2.5 > c
As c is an odd number so c will be equal to 1
c = 1
a = 10 -1
a = 9
The three digit number = 951
The hundred digit is greater than the sum of the tens and ones digits
i hope it will help you!
We are given the expression:
U = E * P
The equality symbol “ = “ means that for all cases, the
value of U and E * P must always be equal. This means that whatever happens on
the left side, must equally happen on the right side.
So what this actually means is that, if we double U so we
must also double the expression E * P, that is:
2 U = 2 (E * P)
However since P stays constant in the process, therefore
only E is changed, hence:
2 U = P * 2 E
So we can see that E is also doubled.